The Economic Implications of the Nazi Concentration Camps: A Historical Reading in the Problematic Concept and Applications of the "Final Solution 1942" Program - Alsultani, Hyder Shakir O. (Al-Adab Journal, 2019)
The research is intended to reassess the official narrative and the interpretive model produced by the Nuremberg Trials on the Nazi extermination of Jews, and to verify the extent of conformity between these claims and the actual historical reality of Nazi policies towards them, by providing a reading of the function of the concentration camps and their relationship to the supposed "genocide program" during the Second World war years. The research is divided into three section: First: Introduction to economic employment of concentration camps. The second was devoted to examining the function of the camps in the light of the forced labor program "Forced labor camps in the light of the economic requirements of the Nazi regime 1939-1941". While the third discussed the problem of the association of the camps with genocide, so came entitled "camps" genocide "problematic characterization and supposed function.